2001
DOI: 10.1021/jp004620y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Orientation and Magnetic Properties of a Single Carbon Nanotube

Abstract: Carbon nanotubes were suspended in carbon tetrachloride and placed in magnetic fields of <80.0 kOe at 310 K. Scanning electron microscopy showed that a single and free nanotube was oriented with the tube axis parallel to the fields. From the Boltzmann distribution of tube directions, the anisotropy of susceptibilities parallel (χ∥) and perpendicular (χ⊥) to the tube axis is estimated to be χ∥ − χ⊥ ∼ (9 ± 5) × 10-6 emu per mole of carbon atoms (χ⊥ < χ∥ < 0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
100
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 39 publications
2
100
0
Order By: Relevance
“…Among them, carbon nanotubes (CNTs) and carbon fibers (CFs) have a large diamagnetic anisotropy owing to their graphene structures; the anisotropy causes a magnetic alignment. This nature of the materials is utilized to fabricate composites in which short CNTs [1][2][3][4] or CFs [5][6][7][8] are aligned in such a manner as to maximally utilize their excellent mechanical, thermal, and electronic properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, carbon nanotubes (CNTs) and carbon fibers (CFs) have a large diamagnetic anisotropy owing to their graphene structures; the anisotropy causes a magnetic alignment. This nature of the materials is utilized to fabricate composites in which short CNTs [1][2][3][4] or CFs [5][6][7][8] are aligned in such a manner as to maximally utilize their excellent mechanical, thermal, and electronic properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, needle-like fiber [1,2], carbon nanotubes [3,4] and inorganic crystals [5][6][7], which are typical one-dimensional materials, have attracted much interest because of their unique properties and potential applications in mechanical, electrical and thermodynamic devices. Chainlike materials are also considered one dimensional.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on the alignment of CNTs by magnetic methods [4][5][6][7][8]. High magnetic fields made it possible to visualize magnetic effects on diamagnetic materials such as CNTs [9].…”
Section: Introductionmentioning
confidence: 99%